BSCI-21 COX4I1 EXPRESSION IN BRAIN METASTASES. (5th August 2022) - Saad, Mahak; Jones, Karra; Loeffler, Bradley; Mott, Sarah; Griguer, Corinne; Monga, Varun
Abstract: BACKGROUND: COX4I1 (Cytochrome C oxidase, subunit 4, isoform 1) is a mitochondrial enzyme involved in the process of switching from glycolysis to oxidative phosphorylation. A previously published prospective biomarker study in glioblastoma cells found that Cytochrome C oxidase (CcO) activity was associated with resistance to treatment with both radiation and temozolomide (TMZ). The current study was designed to retrospectively assess COX4I1 expression in brain metastases from various primary cancers. METHODS: This single-institution, blinded, retrospective biomarker study evaluated 24 patients with paired brain metastases and primary cancers including lung cancer, malignant melanoma, breast cancer, colorectal cancer, renal cell carcinoma, and urothelial carcinoma. COX4I1 immunohistochemical expression in primary and metastatic samples was assessed using the H-score method. A paired t-test was used to assess the difference in total H-score between primary and brain metastasis tissue samples. Cox regression was used to assess the association between COX4I1 expression and overall survival (OS). For OS, time was calculated from metastatic tissue sample retrieval to death due to any cause. RESULTS: Brain metastasis tissue samples were found to have a significantly lower total H-score, on average, when compared to primary cancer tissue samples (p=0.01, mean difference of -33.3). 83.3% of tissue samples from metastases were not radiated. 58.3% of patients were on systemic treatment 6 months prior to tumor resection of brain metastases. COX4I1 expression was not associated with overall survival. CONCLUSIONS: There is significantly increased COX4I1 expression in primary cancers as compared to brain metastases. Anti-cytochrome C oxidase therapies may be beneficial for treatment of primary tumors. No patient or treatment variables were significantly associated with overall survival in paired patients. KEYWORDS: COX4I1, cytochrome c oxidase, brain metastases